Analisis Hukum Terhadap Pertanggungjawaban Anak Perusahaan Kepada Induk Perusahaan dalam Hal Pembagian Keuntungan (Laba Ditahan) Menurut Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas - Triana Maulia Sari (Jurnal Perspektif Hukum, 2021)
The profit obtained by the holding company by investing in shares in a subsidiary company, that is, the holding company gets the profits derived by the subsidiary as much as the shares it owns. The holding company is also entitled to receive dividends from its subsidiaries, provided that it must pay attention to the net income of the subsidiary. As a result of the holding company’s rights to the profits obtained by the subsidiary, the subsidiary has the responsibility to make profits distribution to the holding company. Research uses normative legal research. This study using the statutory approach (statute approach). Data sources used are secondary data, which consists of primary, secondary and tertiary legal materials. Data collection was carried out by means of library study (library research), then processed and analyzed using qualitative analysis method techniques. According to Article 70 of constitution Number 40 Year 2007 Regarding Limited Liability Companies, the company is obliged to prioritize the allowance for reserve funds so that it can cause retained earnings, which is the profit obtained by the company that is not distributed by the company to shareholders in the form of dividends. Subsidiaries are responsible for giving priority to the interests of the company, especially in terms of storing reserve funds that are useful for the interests of the company such as the payment of long-term debts. In addition, retained earnings are used to support the operational activities of subsidiaries